(untitled) (Revista Contexto & Educação, 2024)
Currently, hundreds of science fairs take place across the country. Of different sizes and proportions, each fair makes a huge contribution to the dissemination and popularization of science, in addition to providing students with scientific literacy and personal development. In this study, the purpose is to identify and analyze Brazilian dissertations and theses that deal with the subject of science fairs, focusing on the planning, organization and execution of these events. The objective is to extract, from these productions, elements that contribute to the creation or improvement of similar projects. This is a systematic literature review, outlined in three stages: planning, systematization and qualitative data analysis. The Brazilian Digital Library of Theses and Dissertations, the Brazilian Portal of Open Access Scientific Publications and the Theses and Dissertations Catalog of the Coordination for the Improvement of Higher Education Personnel (CAPES) were used as databases. We found ten dissertations that deal with the theme and approach addressed in this article. Based on the analysis of these dissertations, the results indicate the formation of subcommittees and an organizing committee, in order to contemplate the planning, execution and evaluation of events. We conclude that there is, in this matter, a gap for debate and justifications for new research proposals.